Steps for Education Reform: Methods, Design, Objectives, Personnel, and Support at SDIT Ash Shiddiiqi Jambi City - Siti Roisah; Hendri Wijaya; Mohamad Muspawi; Eva Iryani; Rd M Ali (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: This study aims to describe the steps of educational reform at Ash Shiddiiqi Integrated Islamic Elementary School (SDIT) in Jambi City as an effort to improve the quality of learning and adapt the education system to contemporary developments through the integration of the national curriculum and Islamic values. Background Problems: Educational reform in SDIT faces challenges in effectively integrating innovative learning approaches with Islamic values; therefore, this study focuses on how the steps of educational reform are implemented at SDIT Ash Shiddiiqi Jambi City. Research Methods: This study employs a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation involving the principal, teachers, and educational staff, and were analyzed through data reduction, data display, and conclusion drawing. Finding/Results: The findings indicate that educational reform is carried out through the implementation of student-centered innovative learning methods, the development of an integrative curriculum, the establishment of character- and competency-based educational objectives, the improvement of human resource quality, and strong support from foundations, parents, and the community. Conclusion: Educational reform at SDIT Ash Shiddiiqi Jambi City is implemented in a holistic and integrated manner, contributing to the improvement of learning quality and the strengthening of students’ character, and can serve as a model for Islamic-based education development that is adaptive to contemporary changes.